Esrrb extinction triggers dismantling of naïve pluripotency and marks commitment to differentiation. (1st October 2018) - Festuccia, Nicola; Halbritter, Florian; Corsinotti, Andrea; Gagliardi, Alessia; Colby, Douglas; Tomlinson, Simon R; Chambers, Ian
Abstract: Self‐renewal of embryonic stem cells (ESCs) cultured in LIF/fetal calf serum (FCS) is incomplete with some cells initiating differentiation. While this is reflected in heterogeneous expression of naive pluripotency transcription factors (TFs), the link between TF heterogeneity and differentiation is not fully understood. Here, we purify ESCs with distinct TF expression levels from LIF/FCS cultures to uncover early events during commitment from naïve pluripotency. ESCs carrying fluorescent Nanog and Esrrb reporters show Esrrb downregulation only in Nanog low cells. Independent Esrrb reporter lines demonstrate that Esrrb negative ESCs cannot effectively self‐renew. Upon Esrrb loss, pre‐implantation pluripotency gene expression collapses. ChIP‐Seq identifies different regulatory element classes that bind both OCT4 and NANOG in Esrrb positive cells. Class I elements lose NANOG and OCT4 binding in Esrrb negative ESCs and associate with genes expressed preferentially in naïve ESCs. In contrast, Class II elements retain OCT4 but not NANOG binding in ESRRB‐negative cells and associate with more broadly expressed genes. Therefore, mechanistic differences in TF function act cumulatively to restrict potency during exit from naïve pluripotency. Synopsis: Embryonic stem cell (ESC) populations cultured in LIF‐containing serum heterogeneously express NANOG and ESRRB transcription factors (TFs), and contain both self‐renewing cells as well as cells initiating differentiation. Using fluorescent knock‐in reporters, mouse ESCs are shown to be heterogeneous in self‐renewal, gene expression, and regulatory element activities during exit from naïve pluripotency. Downregulation of NANOG is required for loss of ESRRB in LIF/FCS culture of ESCs. Loss of ESRRB marks commitment to differentiation. Co‐binding of OCT4 at regulatory sites in ESRRB‐high ESCs is differentially dependent on NANOG and other naïve pluripotency TFs. Genes proximal to regulatory elements losing OCT4 binding are preferentially expressed in naïve cells. Abstract : Differential Esrrb transcription factor expression instructs differentiation kinetics of mouse embryonic stem cells.